Nursing professionals’ perception upon the caretaking of children submitted to bone marrow transplantation – A Phenomenological Study - Gomes, Ingrid Meireles; Stelmatchuk, Alzira Maria; Albini, Leomar; Sanches, Eloise Cristina Magajevski; Bueno, Liza Regina da Veiga (Brazilian Journal of Transplantation, 2009)
Highly complex procedures as bone marrow transplantation cause uncertainness, fear, and affliction feelings, mainly when related to Pediatrics, which is a worrying and enchanted theme. Purpose: to understand how nursing professionals perceive themselves upon the attendance of children submitted to bone marrow transplantation. Method: speech analysis by phenomenological approach. Results: two main themes related to the nursing care to children submitted to hematopoietic stem cells transplantation: demand to face constant challenges and difficulties reflected on the need for continuing education and the emotional involvement, spirituality, motherhood and family as present influences. Conclusion: professional lack of preparation in dealing with Pediatrics peculiarities involved in transplant process and the effort of professionals in such kind of service